Cerium-zirconium composite oxide modified nickel-based catalyst and application of cerium-zirconium composite oxide modified nickel-based catalyst in pressurized CH4-CO2 reforming for synthesis gas preparation

By using cerium-zirconium composite oxide-modified nickel-based catalysts, the problem of existing catalysts being prone to carbon deactivation under pressurized conditions is solved, and a catalyst with high reactive activity and anti-carbon deposition properties is achieved, which significantly improves CH4-CO2 Stability and efficiency of reforming reactions.

CN119406416APending Publication Date: 2025-02-11XIAN AERONAUTICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535033.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing nickel-based catalysts are prone to carbon decompression during pressurized CH4-CO2 reforming reaction, and the oxide additive-modified catalyst may experience rapid carbon decompression under pressurized conditions.

Method used

Using cerium-zirconium composite oxide modified nickel-based catalyst, a catalyst of xNi-yCe0.5Zr0.5O2-SiO2 is prepared by uniformly mixing components such as nickel, cerium-zirconium composite oxide and silica, and using this catalyst to pressurize The CH4-CO2 reforming reaction was carried out under conditions.

Benefits of technology

The catalyst showed high reaction activity, excellent anti-carbon accumulation performance and good stability in the pressurized CH4-CO2 reforming reaction, and the methane conversion rate could reach 59%, and remained basically unchanged after 42 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406416A_ABST
    Figure CN119406416A_ABST
Patent Text Reader

Abstract

The invention discloses a cerium-zirconium composite oxide modified nickel-based catalyst and application of the cerium-zirconium composite oxide modified nickel-based catalyst in pressurized CH4-CO2 reforming for synthesis gas preparation. The general formula of the catalyst is xNi-yCe < 0.5 > Zr < 0.5 > O < 2 >-SiO2, in the formula, the value of x is 8%-15%, and the value of y is 2.5%-20%; the preparation method comprises the following steps: dissolving nickel salt, cerium salt and zirconium salt in deionized water, adding into silica sol, adding beta-cyclodextrin, drying, roasting and the like. According to the catalyst disclosed by the invention, the active metal Ni and the formed cerium-zirconium composite oxide are uniformly dispersed in the carrier SiO2, the cerium-zirconium composite oxide remarkably inhibits sintering of metal Ni particles, more oxygen holes can be formed to accelerate elimination of carbon deposit, and the carbon deposit resistance is improved. The raw materials used in the preparation method are cheap, the preparation conditions are easy to control, and the method is simple. The catalyst is used for pressurized CH4-CO2 reforming synthesis gas preparation reaction, the highest methane conversion rate can reach about 59% (750 DEG C, 0.5 MPa) and is close to the thermodynamic equilibrium conversion rate under the reaction condition, and the methane conversion rate is basically kept unchanged after operation for 42 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fossil energy chemical industry, and specifically relates to a cerium-zirconium composite oxide modified nickel-based catalyst and its application in pressurized CH4-CO2 reforming to produce synthesis gas. Background Art

[0002] As a clean energy, natural gas (including oilfield gas, coalbed methane, shale gas, etc.) has attracted much attention for its conversion and utilization. Methane (CH4), as the main component of natural gas, can be utilized in two ways: direct conversion and indirect conversion. Although direct conversion methods such as partial oxidation of methane to methanol and formaldehyde, oxidative coupling to ethylene and ethane, and aromatization to aromatics have the advantages of short reaction routes and simple processes, they are difficult to industrialize due to the difficulty in controlling the reaction process and low product yields. At present, the deep utilization of methane is mainly achieved through the indirect method of preparing chemical products from syngas. As a promising indirect conversion and utilization technology of methane, CH4-CO2 reforming reaction (CRM) can convert CH4 and CO2 into syngas with H2 / CO≤1 and further use it to synthesize carbonyl and oxygen-containing compounds. Given that natural gas is stored and transported under pressure, and chemical production processes such as Fischer-Tropsch synthesis and methanol synthesis that use synthesis gas as raw material also generally adopt pressurized operations, from the perspective of overall energy efficiency and investment cost, pressurized CRM can reduce the reactor size and eliminate the subsequent synthesis gas pressurization operation, making it more reasonable and efficient.

[0003] Nickel-based catalysts have become the most industrially promising CRM catalysts due to their high activity, cheap components and wide sources, but easy carbon deposition and deactivation are their fatal weaknesses. A comprehensive analysis of existing catalyst research shows that the introduction of oxide additives (La2O3, CeO2, Y2O3, ZrO2, Sm2O3, Gd2O3, etc.) to improve the adsorption and activation ability of nickel-based catalysts for CO2 is an effective measure to improve their atmospheric pressure resistance to carbon deposition. However, considering that increasing pressure has a significant impact on the catalytic mechanism, kinetics, and carbon deposition behavior of CRM, catalysts modified with oxide additives may experience rapid carbon deposition and deactivation under pressurized conditions. This has been confirmed by high-throughput screening experiments on related CRM catalysts (Appl. Catal. B: Environ. 105 (2011) 263-275). Therefore, for pressurized CRM, it is imperative to develop oxide-modified nickel-based catalysts and their preparation methods in a targeted manner. Summary of the invention

[0004] The purpose of the present invention is to provide a cerium-zirconium composite oxide modified nickel-based catalyst, which has a simple preparation method and easily controllable reaction conditions, and has high reaction activity, excellent anti-carbon deposition performance and good stability for pressurized CH4-CO2 reforming to produce synthesis gas.

[0005] In order to achieve the above-mentioned purpose, the active component of the cerium-zirconium composite oxide modified catalyst used in the present invention is nickel, the auxiliary component is cerium-zirconium composite oxide, the carrier is silicon dioxide, and the general formula of the catalyst is xNi-yCe 0.5 Zr 0.5 O2-SiO2, wherein x is the mass percentage of Ni in the catalyst, y is the mass percentage of cerium-zirconium composite oxide in the catalyst, the value of x is 8%-15%, and the value of y is 2.5%-20%; the preparation method of the catalyst is: according to the catalyst composition, nickel salt, cerium salt and zirconium salt are dissolved in deionized water, the obtained solution is added dropwise to silica sol under stirring, and β-cyclodextrin aqueous solution is added and stirred for 1.5-3 hours; then the temperature is raised to 60-80°C and stirred until dry, transferred to a blast drying oven at 70-120°C and dried at a constant temperature for 8-12 hours, then transferred to a muffle furnace and calcined at 700-800°C for 4-8 hours, naturally cooled to room temperature, ground, tableted and sieved to obtain 40-60 mesh particles, namely the catalyst.

[0006] In the above catalyst, preferably, the value of x is 10%, and the value of y is 10% to 15%.

[0007] In the preparation method of the catalyst, the nickel salt is nickel nitrate hexahydrate, the cerium salt is cerium nitrate hexahydrate, and the zirconium salt is zirconium nitrate pentahydrate or zirconium oxynitrate (IV) hydrate.

[0008] In the above-mentioned method for preparing the catalyst, the added amount of the β-cyclodextrin is preferably 0.05 to 0.25 times the total molar amount of metal ions in the nickel salt and the zirconium salt.

[0009] In the above-mentioned method for preparing the catalyst, it is preferred to dry the catalyst in a forced air drying oven at a constant temperature of 100 to 110° C. for 8 to 12 hours.

[0010] In the above-mentioned preparation method of the catalyst, it is preferred to calcine at a constant temperature of 750° C. in a muffle furnace for 6 hours.

[0011] The present invention also provides an application of the cerium-zirconium composite oxide modified nickel-based catalyst in pressurized CH4-CO2 reforming to produce synthesis gas. The specific method is: the cerium-zirconium composite oxide modified nickel-based catalyst is loaded into a fixed bed reactor and subjected to H2 high-temperature reduction treatment, and then a CH4 and CO2 mixed gas is introduced at a temperature of 700-800°C, a pressure of 0.1-1.0MPa, a total gas flow rate of 80-150mL / min, and an air velocity of 48000-90000mL@g -1 ·h -1 The synthesis gas is obtained by reforming reaction.

[0012] In the above application, it is preferred that the H2 flow rate of the H2 high temperature reduction treatment is 40-80 mL / min, the reduction temperature is 700-800° C., and the reduction time is 1-2 h.

[0013] In the above application, the CH4 / CO2 molar ratio in the mixed gas is preferably 1 to 2, the temperature is 700 to 800°C, the pressure is 0.5 MPa, the total gas flow rate is 100 mL / min, and the space velocity is 60000 mL@g -1 @h -1 The synthesis gas is obtained by reforming reaction.

[0014] The beneficial effects of the present invention are as follows:

[0015] The active metal Ni and the formed cerium-zirconium composite oxide in the catalyst of the present invention are uniformly dispersed in the carrier SiO2. Compared with the cerium oxide auxiliary agent, the cerium-zirconium composite oxide significantly inhibits the sintering of metal Ni particles, and can form more oxygen vacancies to accelerate the elimination of carbon deposits, thereby improving the anti-carbon deposition performance. The raw materials used in the preparation method of the present invention are cheap, the preparation conditions are easy to control, and the method is simple. The catalyst of the present invention is used for the pressurized CH4-CO2 reforming reaction to produce synthesis gas, and the methane conversion rate can reach up to about 59% (750°C, 0.5MPa), which is close to the thermodynamic equilibrium conversion rate under the reaction conditions, and remains basically unchanged after running for 42 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 10Ni-yCe prepared in Examples 1 to 6 0.5 Zr 0.5 XRD spectra of O2-SiO2-0.05 catalyst and 10Ni-SiO2-0.05 catalyst prepared in Comparative Example 1.

[0017] Figure 2 10Ni-15Ce prepared in Examples 6 to 8 0.5 Zr 0.5 XRD spectra of O2-SiO2-z catalyst and 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3.

[0018] Figure 3 The 10Ni-15Ce prepared in Example 8 0.5 Zr 0.5 XRD spectra of the O2-SiO2-0.2 catalyst after reduction, the 10Ni-SiO2-0.2 catalyst prepared in Comparative Example 2 after reduction, and the 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3 after reduction.

[0019] Figure 4 The 10Ni-15Ce prepared in Example 8 0.5Zr 0.5 H2-TPR diagram of O2-SiO2-0.2 catalyst, 10Ni-SiO2-0.2 catalyst prepared in Comparative Example 2, and 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3.

[0020] Figure 5 The 10Ni-15Ce prepared in Example 8 0.5 Zr 0.5 XRD spectra of O2-SiO2-0.2 catalyst, 10Ni-SiO2-0.2 catalyst prepared in Comparative Example 2 and 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3 after reaction for 42 hours.

[0021] Figure 6 The 10Ni-15Ce prepared in Example 8 0.5 Zr 0.5 TG-DSC graphs of O2-SiO2-0.2 catalyst, 10Ni-SiO2-0.2 catalyst prepared in Comparative Example 2, and 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3 after reaction for 42 hours. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0023] Example 1

[0024] According to the composition of the catalyst: 10% Ni-2.5% Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added is 0.05 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.0722 g (0.17 mmol) of cerium nitrate pentahydrate, and 0.0711 g (0.17 mmol) of zirconium nitrate pentahydrate are dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.1800 g (0.16 mmol) of β-cyclodextrin is dissolved in 90 mL of deionized water to obtain The β-cyclodextrin aqueous solution was obtained; the metal salt aqueous solution was added dropwise to 5.0 g of silica sol and stirred at 400 rpm, and then the β-cyclodextrin aqueous solution was added and stirred for 2 h; then the temperature was raised to 80°C and stirred until dry, and the mixture was transferred to a blast drying oven and dried at 100°C for 12 h, and then transferred to a muffle furnace and calcined at 750°C for 6 h; the mixture was naturally cooled to room temperature, ground, pressed into tablets and sieved to obtain 40-60 mesh particles, and prepared into a catalyst, which was recorded as 10Ni-2.5Ce 0.5 Zr 0.5 O2-SiO2-0.05.

[0025] Comparative Example 1

[0026] In Example 1, cerium nitrate pentahydrate and zirconium nitrate pentahydrate were not added, and the amount of β-cyclodextrin was adjusted to 0.1612 g (0.14 mmol). The other preparation steps were the same as in Example 1 to prepare a catalyst, which was recorded as 10Ni-SiO2-0.05.

[0027] Example 2

[0028] According to the composition of the catalyst 10% Ni-5% Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added was 0.05 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.1491 g (0.33 mmol) of cerium nitrate pentahydrate, and 0.1467 g (0.34 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.2000 g (0.18 mmol) of β-cyclodextrin was dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-5Ce 0.5 Zr 0.5 O2-SiO2-0.05.

[0029] Example 3

[0030] According to the composition of the catalyst: 10% Ni-7.5% Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added was 0.05 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.2310 g (0.53 mmol) of cerium nitrate pentahydrate, and 0.2273 g (0.53 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.2212 g (0.20 mmol) of β-cyclodextrin was dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-7.5Ce 0.5 Zr 0.5 O2-SiO2-0.05.

[0031] Example 4

[0032] According to the composition of the catalyst 10% Ni-10% Ce 0.5 Zr 0.5The amount of O2-SiO2 and β-cyclodextrin added was 0.05 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.3226 g (0.74 mmol) of cerium nitrate pentahydrate, and 0.3165 g (0.74 mmol) of zirconium nitrate pentahydrate were dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.2450 g (0.22 mmol) of β-cyclodextrin was dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps were the same as in Example 1 to prepare a catalyst, recorded as 10Ni-10Ce 0.5 Zr 0.5 O2-SiO2-0.05.

[0033] Example 5

[0034] According to the composition of the catalyst: 10% Ni-12.5% ​​Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added is 0.05 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.4122 g (0.95 mmol) of cerium nitrate pentahydrate, and 0.4055 g (0.95 mmol) of zirconium nitrate pentahydrate are dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.2684 g (0.24 mmol) of β-cyclodextrin is dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps are the same as those in Example 1 to prepare a catalyst, which is recorded as 10Ni-12.5Ce 0.5 Zr 0.5 O2-SiO2-0.05.

[0035] Example 6

[0036] According to the composition of the catalyst 10% Ni-15% Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added is 0.05 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.4955 g (1.14 mmol) of cerium nitrate pentahydrate, and 0.4875 g (1.14 mmol) of zirconium nitrate pentahydrate are dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.2900 g (0.26 mmol) of β-cyclodextrin is dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps are the same as those in Example 1 to prepare a catalyst, which is recorded as 10Ni-15Ce 0.5 Zr 0.5 O2-SiO2-0.05.

[0037] Example 7

[0038] According to the composition of the catalyst 10% Ni-15% Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added is 0.1 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.4955 g (1.14 mmol) of cerium nitrate pentahydrate, and 0.4875 g (1.14 mmol) of zirconium nitrate pentahydrate are dissolved in 40 mL of deionized water to obtain a metal salt solution; 0.5800 g (0.51 mmol) of β-cyclodextrin is dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps are the same as those in Example 1 to prepare a catalyst, which is recorded as 10Ni-15Ce 0.5 Zr 0.5 O2-SiO2-0.1.

[0039] Example 8

[0040] According to the composition of the catalyst 10% Ni-15% Ce 0.5 Zr 0.5 The amount of O2-SiO2 and β-cyclodextrin added is 0.2 times the total molar amount of metal ions. 0.8258 g (2.84 mmol) of nickel nitrate hexahydrate, 0.4955 g (1.14 mmol) of cerium nitrate pentahydrate, and 0.4875 g (1.14 mmol) of zirconium nitrate pentahydrate are dissolved in 40 mL of deionized water to obtain a metal salt solution; 1.1600 g (1.02 mmol) of β-cyclodextrin is dissolved in 90 mL of deionized water to obtain a β-cyclodextrin aqueous solution; the other steps are the same as those in Example 1 to prepare a catalyst, which is recorded as 10Ni-15Ce 0.5 Zr 0.5 O2-SiO2-0.2.

[0041] Comparative Example 2

[0042] In Example 8, cerium nitrate pentahydrate and zirconium nitrate pentahydrate were not added, and the amount of β-cyclodextrin was adjusted to 0.6446 g (0.57 mmol). The other preparation steps were the same as in Example 8 to prepare a catalyst, which was recorded as 10Ni-SiO2-0.2.

[0043] Comparative Example 3

[0044] In Example 8, zirconium nitrate pentahydrate was not added, 0.8244 g (1.90 mmol) of cerium nitrate pentahydrate was added, the amount of β-cyclodextrin was adjusted to 1.0735 g (0.95 mmol), and the other preparation steps were the same as in Example 8 to prepare a catalyst, recorded as 10Ni-15CeO2-SiO2-0.2.

[0045] The catalysts prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were characterized using a D8 Advance X-ray powder diffractometer. Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the catalysts prepared in Examples 1 to 8 all have good NiO dispersibility. Figure 2 It can be seen that compared with the CeO2 characteristic peak of the 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3, the CeO2 characteristic peaks of the catalysts prepared in Examples 6 to 8 are all shifted to a higher angle, indicating that the introduction of ZrO2 and CeO2 forms a cerium-zirconium composite oxide. 0.5 Zr 0.5 The 10Ni-15CeO2-SiO2-0.2 catalyst, the 10Ni-SiO2-0.2 catalyst prepared in Comparative Example 2, and the 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Comparative Example 3 were respectively reduced in pure H2 at a flow rate of 50 mL / min at a heating rate of 15°C / min from room temperature to 750°C for 2 h, and then characterized by XRD. The results are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the catalysts prepared in Example 8 and Comparative Example 3 showed extremely weak characteristic diffraction peaks of metallic Ni after H2 reduction treatment, indicating that the introduction of CeO2 additive and the formation of cerium-zirconium composite oxide can greatly improve the dispersibility of metallic Ni.

[0046] The 10Ni-15Ce prepared in Example 8 was chemisorbed by using AutochemⅡ2950 chemical adsorption instrument. 0.5 Zr 0.5 The 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Example 2, the 10Ni-15CeO2-SiO2-0.2 catalyst prepared in Example 3 were subjected to H2-TPR test. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the catalysts prepared in Example 8 and Comparative Example 3 each have a reduction peak attributable to oxygen vacancies at about 350° C. Obviously, the reduction peak area of ​​the catalyst prepared in Example 8 is significantly larger than the reduction peak area of ​​the catalyst prepared in Comparative Example 3, indicating that the formation of cerium-zirconium composite oxide can significantly increase the oxygen vacancy content.

[0047] Example 9

[0048] The application of the catalysts in Examples 1 to 8 in pressurized CH4-CO2 reforming to produce synthesis gas is as follows:

[0049] 0.1g of catalyst and 1.0g of quartz sand were mixed evenly and placed in the center of the fixed bed reactor. Pure H2 was introduced at a flow rate of 50mL / min under normal pressure, and the temperature was raised from room temperature to 750℃ at a heating rate of 15℃ / min and reduced for 2h. After the reduction was completed, pure N2 was switched to be purged at a flow rate of 50mL / min, and the back pressure valve was adjusted to raise the reactor pressure to 0.5MPa. After the reactor pressure was stable, the reaction was started by switching to a mixed gas with a CH4 / CO2 molar ratio of 1, and the flow rate of the mixed gas was 100mL / min. At a pressure of 0.5MPa, a reaction temperature of 750℃, and a space velocity of 60000mL·g -1 ·h -1 The reforming reaction was carried out for 42 hours under the conditions of , and the gas after the reaction was detected and analyzed online by Pano A91 PLUS gas chromatograph (the chromatographic column was HQ column) after water removal. The experimental results are shown in Tables 1 and 2. At the same time, the catalysts prepared in Comparative Examples 1 to 3 were used for comparative experiments.

[0050] Table 1 Effect of cerium-zirconium composite oxide content on catalyst CH4-CO2 reforming performance

[0051]

[0052] Table 2 Effect of β-cyclodextrin dosage on catalyst CH4-CO2 reforming performance

[0053]

[0054] Note: z in the table represents the dosage of β-cyclodextrin.

[0055] It can be seen from Table 1 that when the cerium-zirconium composite oxide content in Examples 1 to 6 is 2.5% to 15%, the prepared 10Ni-yCe 0.5 Zr 0.5 The O2-SiO2-0.05 catalysts all showed initial activity and catalytic stability superior to those of the 10Ni-SiO2-0.05 catalyst. As shown in Table 2, when the amount of β-cyclodextrin was 0.05 to 0.2 times the total molar amount of metal ions, the 10Ni-15Ce prepared in Examples 6 to 8 0.5 Zr 0.5 The O2-SiO2-z catalysts all showed excellent initial activity and catalytic stability. After 42 hours of reaction, the activity of the catalysts remained basically unchanged, and their stability was better than that of the 10Ni-15CeO2-SiO2-0.2 catalyst and the 10Ni-SiO2-0.2 catalyst.

[0056] The 10Ni-15Ce prepared in Example 8 after 42 hours of reaction was analyzed by using a D8 Advance X-ray powder diffractometer and a STA449 F5 thermal analyzer. 0.5 Zr0.5 The O2-SiO2 catalyst, the 10Ni-SiO2 catalyst of Comparative Example 2, and the 10Ni-15CeO2-SiO2 catalyst of Comparative Example 3 were characterized and analyzed. The results are as follows: Figures 5-6 As shown. Figure 5 It can be seen that the metal Ni diffraction peak intensity of all the catalysts after the reaction is stronger than that of the reduced catalyst ( Figure 3 ), indicating that metal Ni particles sintered in all three catalysts. 0.5 Zr 0.5 The increase in the intensity of the metal Ni diffraction peak of O2-SiO2-0.2 is weaker than that of the catalysts prepared in Comparative Examples 2 and 3, indicating that the formation of cerium-zirconium composite oxide can significantly inhibit the sintering of metal Ni particles. Figure 6 It can be seen that the 10Ni-15Ce prepared in Example 8 0.5 Zr 0.5 The amount of carbon deposits produced on the surface of O2-SiO2-0.2 was the lowest (11.4%), indicating that the formation of cerium-zirconium composite oxide improved the anti-carbon deposition performance of the catalyst.

Claims

1. A cerium-zirconium composite oxide modified nickel-based catalyst, characterized in that: The active component of the catalyst is nickel, the auxiliary component is cerium-zirconium composite oxide, the carrier is silicon dioxide, and the general formula of the catalyst is xNi-yCe 0.5 Zr 0.5 O2-SiO2, wherein x is the mass percentage of Ni in the catalyst, y is the mass percentage of cerium-zirconium composite oxide in the catalyst, x is 8% to 15%, and y is 2.5% to 20%; The preparation method of the catalyst is as follows: according to the catalyst composition, nickel salt, cerium salt and zirconium salt are dissolved in deionized water, added dropwise to silica sol under stirring, and a β-cyclodextrin aqueous solution is added, and stirred for 1.5 to 3 hours; then the temperature is raised to 60 to 80° C. and stirred until dry, transferred to a blast drying oven at a constant temperature of 70 to 120° C. and dried for 8 to 12 hours, then transferred to a muffle furnace and calcined at a constant temperature of 700 to 800° C. for 4 to 8 hours, naturally cooled to room temperature, ground, pressed into tablets and sieved to obtain 40 to 60 mesh particles, namely the catalyst.

2. The cerium-zirconium composite oxidation-modified nickel-based catalyst according to claim 1, characterized in that: The value of x is 10%, and the value of y is 10% to 15%.

3. The cerium-zirconium composite oxidation-modified nickel-based catalyst according to claim 1, characterized in that: The nickel salt is nickel nitrate hexahydrate, the cerium salt is cerium nitrate hexahydrate, and the zirconium salt is zirconium nitrate pentahydrate or zirconium oxynitrate (IV) hydrate.

4. The cerium-zirconium composite oxidation-modified nickel-based catalyst according to claim 1, characterized in that: The added amount of the β-cyclodextrin is 0.05 to 0.25 times the total molar amount of metal ions in the nickel salt, the cerium salt and the zirconium salt.

5. The cerium-zirconium composite oxidation-modified nickel-based catalyst according to claim 1, characterized in that: Dry in a blast drying oven at a constant temperature of 100-110°C for 8-12 hours.

6. The cerium-zirconium composite oxidation-modified nickel-based catalyst according to claim 1, characterized in that: The resulting composites were calcined at 750°C in a muffle furnace for 6 hours.

7. Use of the cerium-zirconium composite oxide modified nickel-based catalyst according to any one of claims 1 to 6 in pressurized CH4-CO2 reforming to produce synthesis gas.

8. Use of the cerium-zirconium composite oxide modified nickel-based catalyst according to claim 7 in pressurized CH4-CO2 reforming to produce synthesis gas, characterized in that: The cerium-zirconium composite oxide modified nickel-based catalyst is loaded into a fixed bed reactor and treated with H2 high-temperature reduction. A mixed gas of CH4 and CO2 is introduced at a temperature of 700-800°C, a pressure of 0.1-1.0 MPa, a total gas flow rate of 80-150 mL / min, and a space velocity of 48000-90000 mL@g -1 @h -1 The synthesis gas is obtained by reforming reaction.

9. Use of the cerium-zirconium composite oxide modified nickel-based catalyst according to claim 8 in pressurized CH4-CO2 reforming to produce synthesis gas, characterized in that: The H2 high temperature reduction treatment has a H2 flow rate of 40 to 80 mL / min, a reduction temperature of 700 to 800° C., and a reduction time of 1 to 2 h.

10. Use of the cerium-zirconium composite oxide modified nickel-based catalyst according to claim 8 in pressurized CH4-CO2 reforming to produce synthesis gas, characterized in that: The CH4 / CO2 molar ratio in the mixed gas is 1-2, the temperature is 700-800°C, the pressure is 0.5MPa, the total gas flow rate is 100mL / min, and the space velocity is 60000mL@g -1 ·h -1 The synthesis gas is obtained by reforming reaction.